The effect of special exercises using different training methods and their effect on VO2MAX and the completion of the 50m freestyle - Ihsan Mohammed Ali (Eximia, 2025)
One of the objectives of the research is to know the effect of using special exercises with different training methods inside the swimming pool as a means of increasing the water resistance to confront the swimmer’s creep forward and its effect on the maximum oxygen consumption and its effect on the time of the 50 m freestyle race. In order to achieve the research goal, the researcher chose (10) swimmers ages (14- 16) years and randomly, and was divided into: Two groups, the first was an experimental group (5) swimmers as an experimental group, and the second was (5) swimmers as a control group. Both groups implemented the sections of the special training program by their trainer in all its details, except that the experimental group used different methods in training as a resistance tool within the vocabulary of the daily training unit. The researcher began testing before and after the research period, which lasted for 12 weeks, with three training units per week. The results achieved were analyzed statistically for the two groups. It was found that the 50-meter freestyle swimming time improved for both groups, but the group that practiced the exercises using different methods became the best. In addition to improving the maximum oxygen consumption, the researcher recommends using special exercises with training methods in the daily training of swimmers because of their impact on achieving the level of achievement in the 50-meter freestyle swimming.